2006
DOI: 10.1107/s1600536806011901
|View full text |Cite
|
Sign up to set email alerts
|

Bis(N-benzoylglycinato)diimidazolecobalt(II)

Abstract: Key indicatorsSingle-crystal X-ray study T = 100 K Mean (C-C) = 0.004 Å R factor = 0.039 wR factor = 0.060 Data-to-parameter ratio = 16.7For details of how these key indicators were automatically derived from the article, see

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…Its molecular and crystal structures were determined by single crystal X-ray diffraction. As expected, Co 2+ is surrounded by four HMPA molecules with T d symmetry as shown in Figure S1 of the Supporting Information . Although the weighted and unweighted agreement factors are relatively large, no significant residual electron density was found in the final Fourier map (Δρ max = 1.030 e – ·Å –3 , Δρ min = −0.730 e – ·Å –3 ).…”
Section: Resultssupporting
confidence: 66%
See 3 more Smart Citations
“…Its molecular and crystal structures were determined by single crystal X-ray diffraction. As expected, Co 2+ is surrounded by four HMPA molecules with T d symmetry as shown in Figure S1 of the Supporting Information . Although the weighted and unweighted agreement factors are relatively large, no significant residual electron density was found in the final Fourier map (Δρ max = 1.030 e – ·Å –3 , Δρ min = −0.730 e – ·Å –3 ).…”
Section: Resultssupporting
confidence: 66%
“…The curve fit using a single Co–O shell indicates that Co 2+ is surrounded by 4.2 O atoms with a Co–O distance of 2.17 Å. The latter is indeed longer than the usual lengths in T d symmetry (typically 1.95 Å found in [Co(HMPA) 4 ] 2+ and ref ), while closer to, but still slightly longer than, those of O h [Co(OH 2 ) 6 ] 2+ (2.06–2.14 Å) . By combining the EXAFS and UV–vis data, it can be concluded that the T d [Co(OH 2 ) 4 ] 2+ is formed in [emim]BF 4 .…”
Section: Resultsmentioning
confidence: 65%
See 2 more Smart Citations